A Tunable Quadrature Oscillator with Only Transconductance Elements and Grounded Capacitors - Iqbal A. Khan; Muslim T. Ahmed; Nigar Minhaj (Active and Passive Electronic Components)
A novel quadrature oscillator is realised with only transconductance elements (TEs) and grounded capacitors. The realised quadrature oscillator uses only two inverting and two non-inverting transconductance elements, along with two grounded capacitors. The quadrature oscillator enjoys the attractive features of low component count, independent frequency tuning and suitability for integration in MOS technology.